Comprendre et intervenir : les connaissances des entraîneurs experts en gymnastique - Cathy Rolland; Marc Cizeron (Activités)
The article presents and discusses the results of a study on the knowleThis paper presents and discusses the results of a study of the knowledge being used by coaches while teaching and correcting athletes’ technical skills in high-level artistic gymnastics. The scientific literature in the field shows that this knowledge is shaped by the coaching situations, in particular their high degree of uncertainty. The study specifically focused on work activity of high-level coaches in gymnastics who must comply with an exacting code of technical, complex skills and their deployment in time and space. The results indicate that for each situation, coaches devise a "diy" theory of individual athletes’ movements and overall activity. Thanks to these cognitive constructs, they achieve an understanding of the complex situations they face and can intervene in ways which integrate that complexity. The implications of these results in terms of designing a coach training setting are discussed, and especially the relevance of case studies to making the requirements of knowledge formalisation compatible with those of the action in context.